2015
DOI: 10.19070/2332-3000-1500019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Habit of Eating Breakfast and Physical Activity on Children Suicidal Behaviour

Abstract: Introduction: Youth suicide is one of the top three causes of death among age group between 15 and 24 years old. The known risk factors include depression, hopelessness, dysfunctional families, substance abuse, school failure and harassment. However, research reports in relation to the protective factors to prevent adolescent from suicidal attempts are still lacking. The purpose of this study is to detect (if any) the protective effect of physical activity and the habit of eating breakfast on children suicidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Students who agreed that there was at least one teacher or adult in their school that they could talk to if they had a problem, were significantly less likely to feel hopeless or suicidal. This is consistent with previous research that found positive teacher‐student relationships contributed as a protective factor against depression in youth 15 . Our findings are unique as they indicate that, regardless of other elements of teacher‐student relationships, adolescents were significantly less likely to report suicidal thoughts if they felt comfortable talking to an adult or teacher about a problem.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Students who agreed that there was at least one teacher or adult in their school that they could talk to if they had a problem, were significantly less likely to feel hopeless or suicidal. This is consistent with previous research that found positive teacher‐student relationships contributed as a protective factor against depression in youth 15 . Our findings are unique as they indicate that, regardless of other elements of teacher‐student relationships, adolescents were significantly less likely to report suicidal thoughts if they felt comfortable talking to an adult or teacher about a problem.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research that found positive teacher-student relationships contributed as a protective factor against depression in youth. 15 Our findings are unique as they indicate that, regardless of other elements of teacher-student relationships, adolescents were significantly less likely to report suicidal thoughts if they felt comfortable talking to an adult or teacher about a problem. Perhaps fostering open communication with non-familial adults encourages children to develop self-reflective and social-emotional competencies that are essential for resiliency-building in the face of hardships.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A healthier diet, by regularly taking breakfast, contributed to a lower suicidal ideation, both as a main effect, and in interaction with cyberbullying victimization and perpetration. Regular breakfast consumption has shown to be associated with better adolescent mental health [44] and lower suicidal ideation [57]. Having a regular and quality breakfast positively impacts mental health by facilitating higher quality-of-life, daily and social activities, social support and physical fitness [58], and getting sufficient nutrients [45], such as restoring levels of glucose needed in the brain after glucose deprivation during the night [59].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Korean National Health and Nutrition Examination Survey (KNHANES), the rate of skipping breakfast rose from 21.4% in 2011 to 23.9% in 2013 (Korea Centres for Disease Control Prevention, 2014). As breakfast consumption is known to be associated with reduced cortisol production (Smith, 2002), which is related to moods, and has been linked to prevention of suicide among children (Wong & Chiu, 2015), it is important to investigate the association between breakfast consumption and depression. However, very few studies have investigated the association between breakfast consumption and depression or mental health.…”
Section: Figure 1 Distribution Of Depression Score and Skipping Breakfastmentioning
confidence: 99%